A Water‐Soluble Cu Complex as Molecular Catalyst for Electrocatalytic CO2 Reduction on Graphene‐Based Electrodes. Issue 3 (29th November 2018) - Wang, Jiong; Gan, Liyong; Zhang, Qianwen; Reddu, Vikas; Peng, Yuecheng; Liu, Zhichao; Xia, Xinghua; Wang, Cheng; Wang, Xin
Abstract: A structurally simple molecular 1, 10‐phenanthroline‐Cu complex on a mesostructured graphene matrix that can be active and selective toward CO2 reduction over H2 evolution in an aqueous solution is reported. The active sites consist of Cu(I) center in a distorted trigonal bipyramidal geometry, which enables the adsorption of CO2 with η 1 ‐COO‐like configuration to commence the catalysis, with a turnover frequency of ≈45 s −1 at −1 V versus reversible hydrogen electrode. Using in situ infrared spectroelectrochemical investigation, it is demonstrated that the Cu complex can be reversibly heterogenized near the graphene surface via potential control. An increase of electron density in the complex is observed as a result of the interaction from the electric field, which further tunes the electron distribution in the neighboring CO2 . It is also found that the mesostructure of graphene matrix favored CO2 reduction on the Cu center over hydrogen evolution by limiting mass transport from the bulk solution to the electrode surface. Abstract : 1, 10‐phenanthroline‐Cu is an active CO2 reduction catalyst on a mesostructured graphene electrode in aqueous solution. The Cu(I) site is reversibly heterogenized near graphene surfaces with potential control to commence catalysis. The mesostructure of graphene suppresses hydrogen evolution by limiting mass transport from electrolyte to electrode, while CO2 reduction is not sensitive to this variation.